Money for Nothin' – Digitalization and Fluid Tax Bases - Mårten Blix; Emil Bustos (Research Institute of Industrial Economics (IFN), 2020)
Technology and digitalization are transforming economic activity, but tax policies are lagging behind. The development also encompasses a broad shift in value-creation, with less emphasis on physical production and more on soft knowledge/intangibles, notably copyrights, firm-specific processes, data and software. We discuss what these changes imply, and we outline the economic factors of scale- and network effects that magnify existing economic trends. A key concern is that the distortionary effects of taxation will become more severe and that tax bases will erode. As factors of production are becoming more fluid and mobile, multinational corporations have been able to shift their profits to low-tax jurisdictions, so called base erosion profit shifting (BEPS). To counter this possibility, a number of governments in 2019 began to unilaterally impose taxes aimed specifically at digital firms. Unless a broad agreement can be reached within the nexus of the more than 130 countries in the OECD/BEPS framework, the existing multinational rule-based order for corporate tax could begin to crumble. On the domestic front, the tax challenges for labour income are, if possible, even more extensive. Although the labour market changes are slower, their key role in public finances imply that even minor reductions result in significant funding challenges. To ensure we get money for somethin', we conclude that a new comprehensive tax reform is urgent.
Keywords: H21; H25; H26; H27; O33; 330; Digital tax; OECD/BEPS; Digitalization; Taxation